JELLY EXTRACT DRINKING RED BIT - Kusumaningrum, Intan; Novidahlia, Noli; Soraya, Dina Ayu (Universitas Djuanda, 2018)
Beets are one of the most useful food ingredients. One of the benefits is to provide natural color in the manufacture of food products. The pigment present in the red bit is betasianin. Betasianin is a class of antioxidants. Drink jelly is a soft gel-shaped drink, generally jelly drinks have elastic properties but consistency or gel strength is weaker than jelly agar. This study aims to diversify food products from red bit beans.The research begins by making red beet extracts first, after which mixing all the ingredients of making jelly drinks. The experimental design used in this research is Completely Randomized Design with three treatment levels and two replications. Data analysis was processed by Kruskal Wallis and ANOVA. The treatments used were comparison of beets and water 1:10, comparison of beets and water 1: 12,5 and comparison of beets and water 1:15. Organoleptic tests used in the study were hedonic rank test and sensory quality test.The results showed that the treatment comparison of beets and water 1:15of was selected jelly beverage based on hedonic test result by panelist. Chemical analysis of the selected product was then performed. Drink jelly comparison of beets and water 1:15 has antioxidant levels of 4.2 mg vit c / 100g sample, food fiber content of 14, 92%, and total sugar of 26.27%.